The Perceptions of Jambi Province Students on the Teaching Profession - Siti Syuhada; Harbeng Masni; Ade Rahima; Erlina Zahar; Wiwik Pudjaningsih; Herman Budiyono; Wennyta Wennyta; Muhammad Halfi Indra Syahputra; Harman Harman; Zuhri Saputra Hutabarat (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this research was to examine how future economics teachers in the province Jambi felt about their practicum experiences and the teaching profession overall. The population of this study is 755, and the approach used is quantitative research with a survey model. The sample comprises students who have successfully completed teaching practice programs, with up to 261 replies. The data was then analyzed using confirmatory factor analysis (CFA), exploratory factor analysis (EFA), and structural equation modelling (SEM). The research's findings include the following: First, students are beginning to have a positive opinion of the teaching profession. Second, by incorporating teaching strategies and models in line with students' present-day technological and time needs, they obtain a greater knowledge of learning media via the experience of teaching practice programs in educational institutions. Third, aspiring teachers are equipped to fulfill the duties of accredited and seasoned educator.